2004
DOI: 10.1007/s10067-004-1017-1
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic microangiopathy with liver, gut, and bone infarction (catastrophic antiphospholipid syndrome) associated with HELLP syndrome

Abstract: Hemolysis, elevated liver enzymes, low platelet count (HELLP) syndrome is a thrombotic microangiopathy complicating pregnancy and shares many clinical and biological features with thrombotic thrombocytopenic purpura (TTP) and hemolytic uremic syndrome (HUS). Thrombotic microangiopathy is also a pathological feature of catastrophic antiphospholipid syndrome (CAPS). An association between refractory HELLP syndrome and antiphospholipid syndrome (APS) has been reported in a few cases. We describe a 19-year-old wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 9 publications
0
20
0
1
Order By: Relevance
“…When erythrocytes pass through the impaired circulation they experience deformation and hemolysis due to mechanical effects (21,22). It has been established that in gestational hypertensive disorders there are changes in the morphology of the erythrocytes (17,23).…”
Section: Resultsmentioning
confidence: 99%
“…When erythrocytes pass through the impaired circulation they experience deformation and hemolysis due to mechanical effects (21,22). It has been established that in gestational hypertensive disorders there are changes in the morphology of the erythrocytes (17,23).…”
Section: Resultsmentioning
confidence: 99%
“…Plusieurs études de cas ont rapporté une forte prévalence des anticorps anticardiolipines et/ou d'anticoagulant circulant en cas de complications hépatiques (infarctus) chez des patientes présentant un HELLP syndrome plus ou moins complet, à des termes le plus souvent très précoces (inférieurs à 24 SA) [16][17][18][19]. Il n'a cependant pas été démontré une corrélation significative entre le HELLP syndrome et la présence d'une thrombophilie qu'elle soit constitutionelle (mutations du facteur V Leiden et de la prothrombine) ou acquise (syndrome des anticorps antiphospholipides) [20][21][22][23][24] [27][28][29].…”
unclassified
“…In two case series, the authors concluded that antiphospholipid antibodies were associated with increased prevalence and severity of HELLP syndrome [56,57]. Moreover, HELLP/CAPS overlap has also been reported in both case reports [58][59][60] and case series [51]. HELLP syndrome is defined as an endothelium-based disorder [61,62].…”
Section: Authors (Reference) Year Clinical Reports Treatment Protocolmentioning
confidence: 96%